A game model in physical education to improve motor skills, cooperation, and discipline of primary school learners - Resti Molina Fizi; Sri Winarni; Guntur; Amri Hartanto (IP Iermakov S.S., 2023)
Background and Study Aim. Motor skills, cooperation, and discipline are important for elementary school children. The purpose of this research is to develop a game-based physical education learning model that is effective in improving motor skills, cooperation, and discipline in elementary school students. Material and Methods. This type of research is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation subjects of the game-based learning model are six expert lecturers with professors and doctoral degrees. The effectiveness test subjects were 46 upper grade elementary school students (aged 10-12 years). The statistical analysis used was Aiken validity analysis and Intraclass Correlation Coefficients, and to analyse the effectiveness of the product using paired sample test analysis. Results. The results show that the game-based learning model is effective for improving motor skills (p-value 0.000 < 0.05), cooperation (p-value 0.000 < 0.05), and discipline (p-value 0.000 < 0.05) in upper grade elementary school students. The developed learning model is valid and reliable, so it is very effective to be used by Physical Education teachers for the learning process. Conclusions. The learning model through this game is expected to be able to bridge the shift in the character values of students in a good direction, along with the development of games and technology that are very strong magnets. For further researchers, further studies and developments are needed to add to the repertoire of game models to improve motor skills, cooperation, and discipline. This will support the learning process of physical education in elementary schools in accordance with the applicable curriculum.